2020
DOI: 10.1186/s13063-020-04413-z
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenergic antagonist for the healing of chronic diabetic foot ulcers: study protocol for a prospective, randomized, double-blinded, controlled and parallel-group study

Abstract: Background: Diabetic foot ulcers (DFUs) are the most common cause of leg amputations and their management is extremely challenging. Despite many advances and expensive therapies, there has been little success in improving outcomes of DFUs. In prior work our laboratory has examined the effects of beta-adrenergic antagonists (βAAs) on skin and skin-derived cells. We have shown that βAAs enhance the rate of keratinocyte migration, promote angiogenesis, and hasten wound healing in scratch wounds in vitro, in anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Esmolol hydrochloride (Galnobax gel formulation), initially developed as a cardioselective beta‐1 receptor blocker, completed Phase 3 studies for the treatment of diabetic foot ulcers. Beta blockers have been shown to enhance the rate of keratinocyte migration, promote angiogenesis, and hasten wound healing [73,74] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esmolol hydrochloride (Galnobax gel formulation), initially developed as a cardioselective beta‐1 receptor blocker, completed Phase 3 studies for the treatment of diabetic foot ulcers. Beta blockers have been shown to enhance the rate of keratinocyte migration, promote angiogenesis, and hasten wound healing [73,74] …”
Section: Resultsmentioning
confidence: 99%
“…Beta blockers have been shown to enhance the rate of keratinocyte migration, promote angiogenesis, and hasten wound healing. [73,74] Under small-molecule-related synthesis and process R&D we have included synthetic chemistry as well as biotransformations, unless these provided merely access to early-stage starting materials, intermediates or chemicals with multiple applications, which were ranked under industrial biotechnology. Examples are deuterium-labelled glucuronides for metabolism studies, paclitaxel, deacetyl-cephalosporin, lipstatin, levodopa, and semi-synthetic artemisinin.…”
Section: A Small-molecule Therapeuticsmentioning
confidence: 99%
“…10 Kaur et al showed that timolol was effective in chronic diabetic foot ulcers. 11 The studies of Braun et al and Vestita et al showed the efficacy of timolol in the management of chronic recalcitrant wounds. 12,13 Similarly, there have been many cases reported where chronic wounds were successfully treated with topical timolol.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic wounds are typically characterized by delayed epithelialization, a persistent inflammatory response, infection, and impaired vascular‐neural function 90 . These pathological alterations prevent the damaged tissue from completing healing through the normal healing process, causing vascular ulcers, diabetic chronic ulcers, pressure wounds, and other complex wounds 91 . The formation of ulcers lengthens hospital stays, raises treatment costs, and results in significant physical, psychological, and financial burdens on patients 92 .…”
Section: Application Of β‐Blockers In Soft Tissue Wound Healingmentioning
confidence: 99%